EVALUASI KINERJA ALAT MILL FAN DI CEMENT MILL PADA PT SEMEN BATURAJA PERSERO Tbk. - Sari, Ricka Puspita; Safaruddin, Safaruddin; Anugrah, Rendotian (Jurnal Multidisipliner Bharasumba, 2022)
At PT. Semen Baturaja has a series of routine evaluation activities to determine the performance/performance of the equipment contained in the cement mill of the Baturaja Factory. In the cement mill there are various kinds of tools that are used, one of which is a mill fan. Mill fan is a tool used to generate air flow in the mill air flow system so that the milling process, moisture reduction, separation, and material transport take place perfectly. From this understanding, it can be analyzed that the mill fan is a tool used to circulate mill air flow. Keywords: PT. Semen Baturaja, Evaluation, Mill fan,Cement Mill